การใช้ซอร์บิแทนเอสเตอร์ทดแทนสารลดแรงตึงผิวสังเคราะห์ในการผลิตเชื้อเพลิงชีวภาพจากน้ำมันปาล์มโดยวิธีไมโครอิมัลชัน - ณัฐพร สรสุชาติ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The current energy and environmental issues lead to the study and development of the production of biofuels from vegetable oil. Biofuel, a clean energy, can reduce the dependence on imported petroleum. However, direct use of vegetable oil can cause engine durability problems due to their high viscosity. Microemulsion is one of the methods that can be used to improve the properties of vegetable oil. In the process, ethanol is used to reduce the viscosity of the vegetable oil while surfactants and co-surfactants are used to formulate reverse phase micelles. This study investigates the application of sorbitan esters as alternative of synthetic surfactants to produce microemulsion based biofuel. Three sorbitan esters, sorbitan monolaurate (span20), sorbitan monooleate (span80), and sorbitan trioleate (span85) and three alcohol (butanol, hexanol, and octanol) were used as surfactants and co-surfactants, respectively. It was found that palm oil blend with diesel at a ratio of 1:1 by volume at 60 percent by total volume, span 80 mixed with octanol at a ratio of 1:8 by mole at 20 percent by total volume, and ethanol purity 99 percent at 20 percent by total volume could be used to formulated biofuel at the smallest volume fraction. The properties of microemulsion based biofuel depends on the properties of the sorbitan esters and alcohol. The results show that microemulsion with appropriate sorbitan esters can be used to produce biofuel with comparable properties to those of biodiesel.